Transmission-blocking interventions eliminate malaria from laboratory populations - Blagborough, A; Churcher, T; Upton, L; Ghani, A; Gething, P; Sinden, R (Springer Nature, 2013)
Transmission-blocking interventions aim to reduce the prevalence of infection in endemic communities by targeting Plasmodium within the insect host. Although many studies have reported the successful reduction of infection in the mosquito vector, direct evidence that there is an onward reduction in infection in the vertebrate host is lacking. Here we report the first experiments using a population, transmission-based study of Plasmodium berghei in Anopheles stephensi to assess the impact of a transmission-blocking drug upon both insect and host populations over multiple transmission cycles. We demonstrate that the selected transmission-blocking intervention, which inhibits transmission from vertebrate to insect by only 32%, reduces the basic reproduction number of the parasite by 20%, and in our model system can eliminate Plasmodium from mosquito and mouse populations at low transmission intensities. These findings clearly demonstrate that use of transmission-blocking interventions alone can eliminate Plasmodium from a vertebrate population, and have significant implications for the future design and implementation of transmission-blocking interventions within the field.